Nursing administration handbook - Rowland, Howard S.;Rowland, Beatrice L. (Gaithersburg, Md. : Aspen Publishers, 1992)
Fresh insights regarding management techniques and innovative state-of-the-art management approaches required that major new sections be introduced in most of the chapers.
pt. I. Management -- pt. II. The working environment -- pt. III. Administration -- pt. IV. Operations -- pt. V. Human resources management -- pt. VI. Opportunities for the nursing service and administrator.
Includes index.
Keywords: NURSING SERVICES -- ADMINISTRATION